Srategi Integrasi Nilai Islam dalam Pembelajaran Matematika untuk Mewujudkan Karakter Siswa Jujur dan Adil di Madrasah Aliyah Negeri 1 Wonosobo - Edi Sugiman; Nurul Mubin; Moh.Sakir (CV. Aksara Global Akademia, 2025)
Mathematics is a universal science that underlies the development of modern science and technology, and has an important role in the development of human thinking. Mathematics is a subject that is based on logical, rational, critical, and systematic thinking patterns. Religion and rationality are two perspectives that have a strong influence. Humans view religious values ​​and rational values ​​as different entities, causing a dichotomy paradigm, especially in the realm of education. In the perspective of the epistemology of science in Islam, Islam and science are complementary and interdependent entities. The mathematical approach used here does not mean that Islamic values ​​are low, but only to increase the belief of Muslims that all knowledge is valuable and can lead to true goodness and increase faith and closeness to Allah SWT.To examine how Islamic values ​​are applied in mathematics learning, To identify and develop effective strategies or methods in integrating Islamic values ​​in mathematics learning materials, To measure the extent of the application of Islamic values ​​in mathematics learning.This study uses a qualitative approach, while the type of research used by the researcher is descriptive research.Mathematics as a logical and systematic science, has a meeting point with Islamic teachings that emphasize truth, justice, and balance. For example, the concept of monotheism can be associated with the order of the universe expressed through mathematical formulas, fostering a sense of gratitude and obedience. The implementation of Islamic values ​​that are rahmatan lil 'alamin (blessing for all nature) in mathematics learning, especially to form honest and fair characters in students.